New in The Tropical Agriculturalist series [3] - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Camels by R T Wilson 1998. 144 pp. ISBN 0 333 60083 5 CTA number 880